Efficacy of Antirabies IgG and IgY on Protection of Mice against Experimental Viral Infection as a Model for Emergency Intervention (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: rabies; vaccine; antirabies IgY; antirabies IgG; emergency